Introducción a la estadística descriptiva con R - Aguilar Fernández, Eduardo (Editorial Universidad Nacional (EUNA), 2020)
The objective of this document is to offer all the people who take their first steps in R language, a first approach to the environment through the execution of basic commands. The target audience can be defined mostly by students of courses where issues pertaining to descriptive statistics are addressed, it can also be useful for people with more knowledge as a source of consultation, as well as support for teaching staff who desire to teach their classes using this tool.